Trusting enemies: Interpersonal relationships in international conflict, by Nicholas J. Wheeler, Oxford, Oxford University Press, 2018. Issue 1 (2nd January 2019) - Hosking, Geoffrey A.
ABSTRACT: This book review relays key theoretical points put forward by Nicholas J. Wheeler in his book Trusting Enemies, in particular how face-to-face bonding between state leaders is essential for building trust between states in conflictual relationships. The reviewer, Geoffrey A. Hosking, supports many of the arguments put forward by Wheeler but also challenges some ideas around how identity and suspension played out in trust building in the historical cases presented in the book. He suggests additional explanations and issues, such as the background work of other officials. The review also covers the notion of security communities and highlights possible deeper insights into their development. It ends by pointing out how timely, telling and necessary Wheeler's analysis is given the current international relation challenges.